Anthropometric measurements of term singletons at 6 years of age born from fresh and frozen embryo transfer: A multicenter prospective study in Japan - Keiko Ueno; Junya Kojima; Kohta Suzuki; Akira Kuwahara; Yasuhiko Higuchi; Atsushi Tanaka; Takafumi Utsunomiya; Yasuyuki Mio; Hirotaka Nishi; Yasunori Yoshimura; Minoru Irahara; Naoaki Kuji (Reproductive Medicine and Biology, 2023)
Abstract Purpose The purpose of this study is to compare anthropometric measurements between term singletons conceived via fresh embryo transfer (FreET) and frozen embryo transfer (FET) and those born via natural conception (NC) or fertility treatments milder than assisted reproductive technology (non‐ART) at 6 years of age. Methods A total of 8149 children were enrolled, and questionnaires about anthropometric measures (weight, height, BMI) were addressed to parents, when the children were 1.5, 3, and 6 years of age. A total of 3299 term singletons were enrolled at birth: 533, 476, 916, and 1374 in the NC, non‐ART, FreET, and FET groups, respectively. Results A total of 1635 term singletons (290, 176, 467, and 702 in the NC, non‐ART, FreET, and FET groups respectively) were enrolled until 6 years of age (follow‐up rate, approximately 50%). When non‐ART group was used as control, the FreET children were 1.0 cm taller than the non‐ART children at 6 years of age, after adjusting for confounding factors. However, no differences were observed in the anthropometric data among the non‐ART, ART, and NC children at 6 years of age. Conclusion At 6 years of age, term singletons were taller in the FreET group than in the non‐ART group, after adjusting for confounders.